Antecedents of Student Loyalty in Open and Distance Learning Institutions: An Empirical Analysis - Daud, Yon Rosli; Mohd Amin, Mohd Rushidi bin; Abdul Karim, Jeannot bin (International Review of Research in Open and Distributed Learning, 2020)
The purpose of this research is to examine the relationship between factors leading to student loyalty in open and distance learning universities. Specifically, this research explores the relationship between perceived service quality, perceived e-service quality, and university image as mediators of student loyalty in Open University Malaysia (OUM). Data were collected from 16 OUM learning centres throughout Malaysia. A purposive stratified convenience sampling technique was applied and a sample size of 752 respondents was obtained. The data indicated that perceived service quality has a positive and significant relationship with both university image and student loyalty. Similarly, it was found that perceived e-service quality has a positive significant relationship with both university image and student loyalty. University image acted as a mediator both in the relationship between perceived service quality and student loyalty, and in the relationship between perceived e-service quality and student loyalty.